Hubungan antara Lingkungan Organisasi dan Administrasi dalam Penggunaan Sistem Informasi Manajemen: Studi Etnografi pada Instansi Pemerintah - Munawaroh, Kholifatul; Amanda, Septiyan Dwi (Government Science Department , Faculty of Social and Political Science - University of Lampung. Journal of Government and Social Issues (JGSI), 2025)
This study aims to analyze the implementation of Management Information Systems (MIS) in the Bandar Lampung City Trade Office by highlighting the adaptive interaction between the organizational environment and public administration practices. Using an ethnographic-based qualitative approach, this study explores how employees adapt to digital policies, how communication and coordination patterns are formed, and how the dynamics of bureaucratic work change in the context of information technology implementation. The results show that MIS can improve administrative efficiency, accelerate reporting, and strengthen the transparency and accountability of public services. The transformation from manual to digital processes creates a data-driven work culture and improves cross-departmental coordination. However, a number of challenges remain, such as infrastructure limitations, digital competency gaps, and the need for ongoing training. In addition, leadership has proven to play a crucial role through supervision, motivation, and support for employees during the adaptation process. Theoretically, this research enriches the study of organizational ecology in the context of public sector digitalization. Practically, these findings emphasize the importance of strengthening human resource capacity and transformational leadership for the sustainability of MIS implementation.